Fluid pressure optimization of a PID-controlled hydraulic jack for enhanced lifting efficiency and stability - Hairil Budiarto; Ibnu Irawan; Achmad Imam Sudianto; Ahmad Sahru Romadhon (Jurnal Polimesin, 2025)
Hydraulic and mechanical jacks are widely used for lifting applications but face limitations in efficiency and load handling. Despite being powerful, hydraulic jacks are prone to pressure loss and fluid leakage under static load, while mechanical systems lack automation and practicality. This research presents a hybrid hydraulic jack system integrating a DC motor-driven screw actuator and proportional–integral–derivative (PID) control for adaptive fluid pressure regulation. The purpose of this research is to develop an automatic hydraulic jack that integrates mechanical and hydraulic systems to improve the efficiency of load lifting time and reduce the risk of fluid leakage due to prolonged static pressure. The system was tested under three different loads: 90 kg, 110 kg, and 130 kg, with corresponding pressure setpoints of 170, 195, and 223 psi. Using the Ziegler–Nichols tuning method, the PID controller achieved high accuracy with error deviations of 1.1 psi, 0.1 psi, and 1.5 psi, respectively. These results represent a 95–99% precision rate in pressure regulation, compared to uncontrolled systems. The findings demonstrate the ability of the system to maintain pressure stability under varying load conditions, therefore reducing the risk of leakage and mechanical fatigue. This PID-based jack offers a cost-effective and efficient alternative to conventional power-pack hydraulic systems, particularly in mobile or resource-constrained applications.